PVA/Graphene nanocomposite: morphology and its thermal properties - Abu Hannifa, Abdullah; Zulhelmi, Ismail; Anis Sakinah, Zainal Abidin; Fadwa Sameeha, Ismail; Kamal, Yusoh (IOP Publishing Ltd, 2018)
Graphene is known as a wonder materials that can be used to enhance the properties of nanocomposites. In this work, PVA/Graphene nanocomposite was fabricated using simple solution method. The photograph of the nanocomposite samples shown the transparency of the sample reduced as the graphene content increase. The photograph also shown the PVA and the modified graphene are miscible and compatible. The XRD of the samples proved the exfoliation of graphene in the nanocomposite and the result of the thermal property improvement for the sample is confirmed by the TGA.